Effect of Fungicides on Southern Rust of Corn - E. A. Adee; S. Duncan (Kansas Agricultural Experiment Station Research Reports, 2018)
The decision to apply fungicides to corn is not an easy decision in Kansas, especially when grain prices are low. Numerous factors determine what diseases are present, and whether the plants will be defoliated enough to reduce yield. Correctly identifying the disease, knowing what environmental conditions favor the development of an epidemic, and knowing the hybrid’s resistance to the diseases can be known before making the decision. However, knowing if the conditions will be favorable for the spread of the disease up the plant is very unpredictable. A situation like a ‘perfect storm’ for foliar diseases defoliating corn occurred in 2017. Southern rust was present at tasseling, much earlier that most years, and it had the ability to spread quickly in the relatively cool (80 to 90°F) and wet conditions that occurred in August. Additionally, many of the corn hybrids didn’t have high levels of resistance to southern rust.
Keywords: corn; fungicide; southern rust; strobilurin; foliar disease; gray leaf spot